Clinical investigation of back disorders in horses: a retrospective study (2002-2017) - Mayaki, Abubakar Musa; Abdul Razak, Intan Shameha; Mohd Adzahan, Noranizan; Mazlan, Mazlina; Adamu, Lawan; Abdullah, Rasedee (Veterinary World, 2019)
Background and Aim:VBack disorder is an ailment that often affects athletic and riding horses. Despite the rapidly growing equine athletic and equestrian activities, there is no documentation on the nature of equine back disorder (EBD) in Malaysian horses. The purpose of this study was to characterize EBD cases presented to University Veterinary Hospital, Universiti Putra Malaysia, between 2002 and 2017. Materials and Methods: The compilation of data was based on signalment, case history, duration of clinical signs, anatomical location of the pain, method of diagnosis, type of EBD, treatment, and outcome. The diagnosis of EBD was based on a history of poor performance, clinical examination findings, radiography, and, where applicable, necropsy. Results: A total of 181 diagnosed cases of EBDs were identified. The age of horses ranged from 5 to 22 years. The EBD cases were more prevalent in male than female horses and predominantly in geldings (60.77%). Thoroughbred, Arab, Polo pony, and Warmblood also recorded the most EBD cases among breeds. The discipline of horses tended to influence the development of EBDs, with patrolling horses recording the highest frequency. Most EBD cases were of the primary type (92.27%), with the main causes being soft-tissue lesions (57.48%), vertebral lesions (18.56%), tack-associated problems (16.77%), and neurological lesions (7.19%). The common treatments employed were administration of nonsteroidal anti-inflammatory agents, 1 to 3-month rest, warm and cold compression therapy, massage therapy, exercise adjustment, as well as correction of ill-saddle fit. Conclusion: Most EBDs in this study were associated with soft-tissue lesions. Among vertebral lesions, kissing spines were the most common cause of EBDs in horses in Malaysia.